Peningkatan Prestasi Belajar Dengan Model Problem Based Learning Materi Skala Pada Siswa Kelas V - Danang Jatmiko; Rusmawan Rusmawan; Kensi Jati Hananingrum (Universitas Muhammadiyah Magelang, 2023)
This study aims to improve student learning achievement by using the Problem Based Learning (PBL) model on the scale material for fifth grade students at Kanisius Totogan Elementary School. This type of research uses Classroom Action Research which is carried out in two cycles with four stages, namely planning, action, observation, and reflection. The data analysis technique uses quantitative descriptive so that it can describe data about the value of student achievement in the form of evaluation results of tests carried out at the end of learning. From the results of the Classroom Action Research that has been carried out, it is obtained data that in the pre-cycle the students' learning completeness was only 28.6% with an average value of 59.5. Then in the implementation of cycle 1, the students' learning completeness increased to 64.3% with an average score of 74. Then in the implementation of cycle 2, the proportion of students' learning mastery increased to 85.7% with an average score of 81.9. Thus it can be concluded that the application of the Problem Based Learning (PBL) learning model can improve learning achievement of the Scale material in class V SD Kanisius Totogan. Keywords: learning achievement, Problem Based Learning